Coating modification method and application of Prussian blue analogue
By coating the Prussian blue analog with poly3-hexylthiophene (P3HT), the crystal water is restricted in the crystal structure, which solves the battery performance problem caused by the desorption of crystal water and achieves the structural stability and electrochemistry of the modified Prussian blue analog. Performance improvements.
Patent Information
- Application Number
- CN202411271684.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The existing Prussian blue analogues are difficult to effectively solve these problems due to the detachment of crystallization water during the battery cycle.
Poly-3-hexylthiophene (P3HT) is used to coat Prussian blue analogues to restrict crystallization water in the crystal structure so that it cannot escape, thereby stabilizing the crystal structure and improving electrochemical performance.
Through coating modification, the structural stability and electrochemical performance of the modified Prussian blue analogues are improved, battery performance problems caused by the desorption of crystal water are solved, and the cycle capacity retention rate and battery cycle stability are significantly improved.
Smart Images

Figure CN119320574A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material modification, and in particular relates to a coating modification method of a Prussian blue analogue and application thereof. Background Art
[0002] Prussian Blue (PB) and Prussian Blue Analogues (PBAs) have an open framework structure with large ion channels and gaps in the lattice, making them one of the few species that can accommodate K + One of the host materials, very conducive to K + Or Na + However, the main synthesis method of Prussian blue analogues is the coprecipitation method in aqueous solution. This method will inevitably produce a large amount of crystal water in the crystal. The crystal water will participate in the battery cycle decomposition in the battery, causing the battery internal resistance to increase, resulting in rapid capacity decay. At the same time, the crystal water will repel the K + Or Na + , resulting in crystal defects. Current research suggests that reducing the crystalline water content in the crystal to improve the crystal completion of Prussian blue analogs plays a vital role in improving their electrochemical performance.
[0003] A study reported that the molecular formula is K 0.220 Fe[Fe(CN)6] 0.805 ·4.01H2O Prussian blue analogs (PBAs) positive electrode materials. During the battery cycle, the crystal water in the above PBAs will flow with K + The water is deintercalated and enters the electrolyte, and the water is oxidized and decomposed at a high potential, which will not only affect the initial coulombic efficiency, but also increase the internal resistance of the battery, resulting in a decrease in the cycle capacity. At the same time, the lattice stability of the material itself will also be affected by the release of crystal water. There are also studies that synthesized PBAs and dried them at 100°C in a vacuum state and in air respectively. The chemical formulas of the dried products are Na 1.89 Mn[Fe(CN)6] 0.97 ·0.3H2O and Na 1.89 Mn[Fe(CN)6] 0.97·1.87H2O, the water content of PBAs obtained by the two drying methods is quite different, and among them, PBAs with less water content show a reversible capacity of 150mAh / g, and have very good rate performance and cycle performance. This study shows that thermal removal of interstitial water in PBAs will have a great impact on its electrochemical performance. So far, research on PBAs has focused on how to reduce the crystallization water of PBAs, that is, to reduce the content of crystallization water of the material as much as possible during synthesis, improve the integrity of the material crystal, and thus improve the electrochemical performance of the material. It is difficult to completely avoid the generation of crystallization water during the synthesis of PBAs, and the most direct way to remove crystallization water is heating, but simply heating and drying, blindly reducing crystallization water may cause the PBA crystal structure to be unstable, affecting the cycle performance, and heating cannot completely remove all crystallization water, and it is still difficult to solve the negative problems caused by crystallization water to battery performance. Summary of the invention
[0004] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a coating modification method of a Prussian blue analogue, which not only stabilizes the crystal structure of PBAs, but also solves the negative problems caused by crystal water during use, thereby improving the performance of PBAs.
[0005] The second object of the present invention is to provide a modified Prussian blue analogue obtained by the above-mentioned coating modification method.
[0006] A third object of the present invention is to provide an application of the modified Prussian blue analogue.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present invention provides a method for coating and modifying a Prussian blue analogue, comprising the following steps: mixing poly (3-hexylthiophene), a Prussian blue analogue and a solvent, so that at least a portion of the poly (3-hexylthiophene) coats the Prussian blue analogue, and removing the solvent to obtain the coated and modified Prussian blue analogue.
[0009] The inventive concept of the present invention is as follows: the present invention is different from the prior art in that it focuses on reducing the content of crystal water in the material, but starts from another angle, focusing on limiting the escape behavior of crystal water during use to avoid the influence of crystal water on the performance. Specifically, poly 3-hexylthiophene (P3HT) is used to coat PBAs, so that crystal water cannot escape during the battery cycle, and at the same time, it can stabilize the crystal structure of PBAs and improve its electrochemical performance. In addition, the presence of crystal water in the crystal can also shield K + Or Na + Interaction with structural anions, thereby increasing the K+ or Na + Diffusion ability to further improve the electrochemical performance of PBAs.
[0010] Preferably, the solvent includes at least one of chloroform, carbon disulfide, chlorobenzene, toluene, tetrahydrofuran, o-dichlorobenzene, p-dichlorobenzene, or dimethylformamide; more preferably, the solvent includes at least one of chloroform, carbon disulfide, chlorobenzene, or toluene; even more preferably, the solvent is selected from chloroform.
[0011] The solvent used in the present invention needs to have good solubility in poly(3-hexylthiophene), which is conducive to more fully dispersing poly(3-hexylthiophene) and achieving a good coating effect on the Prussian blue analog. Poly(3-hexylthiophene) has a large solubility in chloroform and can achieve a better coating effect in the present invention.
[0012] Preferably, the chemical formula of the Prussian blue analog is A x M′[M″(CN)6] y ·nH2O, 0 < x ≤ 2, 0 < y ≤ 1, 0 < n ≤ 4, where A is an alkali metal element, and M′ and M″ are each independently a transition metal element.
[0013] Preferably, the alkali metal element includes at least one element of Li, Na, or K.
[0014] Preferably, the transition metal element includes at least one element of Fe, Co, Cu, Mn, or Ni.
[0015] In some specific embodiments of the present invention, in the chemical formula of the Prussian blue analog, 0.5 ≤ x ≤ 2; in some specific embodiments of the present invention, in the chemical formula of the Prussian blue analog, 1 ≤ x ≤ 2; non-limiting specific examples are that x is 1.2, 1.4, 1.5, 1.8, or 2.
[0016] In some specific embodiments of the present invention, in the chemical formula of the Prussian blue analog, 0.2 ≤ y ≤ 1; in some specific embodiments of the present invention, in the chemical formula of the Prussian blue analog, 0.5 ≤ y ≤ 1; non-limiting specific examples are that y is 0.6, 0.7, 0.8, 0.9, or 1.
[0017] In some specific embodiments of the present invention, in the chemical formula of the Prussian blue analog, 0.2 ≤ n ≤ 3.5; in some specific embodiments of the present invention, in the chemical formula of the Prussian blue analog, 1.5 ≤ n ≤ 3; non-limiting specific examples are that n is 1.8, 2, 2.3, 2.5, or 2.8.
[0018] In some specific embodiments of the present invention, the chemical formula of the Prussian blue analogue is K2FeFe(CN)6·2.3H2O.
[0019] Preferably, the mass ratio of the poly 3-hexylthiophene to the Prussian blue analog is 1:(10-35); more preferably 1:(15-25); more preferably 1:(18-22); non-limiting examples include 1:19, 1:20 or 1:21.
[0020] Preferably, the mass ratio of the poly (3-hexylthiophene) to the solvent is 1:(15-25); more preferably 1:(18-22); non-limiting examples include 1:19, 1:20 or 1:21.
[0021] Preferably, in the coating modification method of the Prussian blue analogue, the mixing time is 0.1 to 20 hours; more preferably 0.5 to 12 hours.
[0022] Preferably, in the coating and modification method of the Prussian blue analogue, the solvent is removed by drying.
[0023] Preferably, the drying temperature is 60-100°C; more preferably 70-90°C; further preferably 75-85°C.
[0024] Preferably, the drying time is 5 to 30 hours; more preferably 8 to 25 hours; and even more preferably 10 to 20 hours.
[0025] In some specific embodiments of the present invention, the mixing is specifically: firstly mixing the poly (3-hexylthiophene) and the solvent, and then adding the Prussian blue analogue and mixing.
[0026] Firstly, the poly (3-hexylthiophene) and the solvent are fully mixed, and then the Prussian blue analog is added, which is conducive to achieving a better coating effect on the Prussian blue analog.
[0027] The second aspect of the present invention provides a modified Prussian blue analogue obtained by the coating modification method described in the first aspect of the present invention.
[0028] Preferably, the water content of the modified Prussian blue analogue is 8 to 20 wt %; more preferably, it is 9 to 18 wt %; and even more preferably, it is 10 to 15 wt %.
[0029] The third aspect of the present invention provides a use of the modified Prussian blue analogue described in the first aspect of the present invention in preparing a positive electrode material for a battery.
[0030] Preferably, the battery comprises a potassium ion battery or a sodium ion battery.
[0031] The beneficial effects of the present invention are as follows: the present invention adopts poly 3-hexylthiophene (P3HT) to coat the Prussian blue analogue, and the crystal water is restricted in the crystal structure, so that it cannot escape during use, and the structural stability of the modified Prussian blue analogue is effectively improved, and the use performance thereof is also improved. When the modified Prussian blue analogue obtained by the method of the present invention is used as a positive electrode material of a battery, the crystal water can be prevented from escaping during the battery cycle, and while stabilizing the crystal structure of the positive electrode material, the problem of oxidative decomposition caused by the crystal water entering the battery electrolyte is solved, and the battery cycle performance is effectively improved. Therefore, the modified Prussian blue analogue of the present invention has a wide range of applications in the preparation of positive electrode materials for batteries.
[0032] Specifically, compared with the prior art, the present invention has the following advantages:
[0033] 1. The method of the present invention can be applied to finished PBAs containing a large amount of crystal water without changing their crystal structure. The method has a wide range of applications and is conducive to fundamentally solving the adverse effects of crystal water on PBAs. When applied to the positive electrode of a battery, it has the advantages of good safety, low price, high capacity, and high cycle life.
[0034] 2. When the modified Prussian blue analogue prepared by the present invention is used as the positive electrode material of potassium ion battery or sodium ion battery, the presence of crystal water in the crystal can also shield K + Or Na + Interaction with structural anions, thereby increasing the K + Or Na + Diffusion capacity can further improve the electrochemical performance of the positive electrode material.
[0035] 3. The coating modification method of the present invention is simple, and the obtained modified Prussian blue analogue has good electrochemical properties and is widely used in the preparation of battery positive electrode materials, especially positive electrode materials for potassium ion batteries or sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The figure is a flow chart of the coating modification method of the Prussian blue analogue in the embodiment of the present invention.
[0037] Figure 2 The XRD diagrams of the samples of Example 1 and Comparative Examples 1-2 are shown.
[0038] Figure 3 The electrochemical performance diagram of the samples of Examples 1 to 3 and Comparative Example 1.
[0039] Figure 4 The infrared spectra of the samples of Example 2 and Comparative Example 1 before and after the cycle test.
[0040] Figure 5Infrared spectrograms of the samples of Example 1 and Example 3 before and after cyclic testing. Detailed implementation mode
[0041] The content of the present invention will be further described in detail through specific examples below. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the protection scope of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles described in the present invention all fall within the protection scope of the present invention. The specific process parameters and the like in the following examples are also only an example within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description in this article, rather than being limited to the specific data in the following examples. The raw materials, reagents or devices used in the following examples and comparative examples can be obtained from conventional commercial channels without special instructions, or can be obtained by existing known methods.
[0042] In some embodiments of the invention, the chemical formula of the Prussian blue analogue is A x M′[M″(CN)6] y ·nH2O, 0 < x ≤ 2, 0 < y ≤ 1, 0 < n ≤ 4, where A is an alkali metal ion such as Li, Na, K, etc.; M′ and M″ are transition metal ions such as Fe, Co, Cu, Mn, Ni, etc., and M′ and M″ can be the same or different. In some specific embodiments of the invention, the Prussian blue analogue also contains vacancy defects, and the number of vacancy defects is related to the number of [M″(CN)6], specifically 1 - y.
[0043] An embodiment of the present invention provides a method for coating and modifying a Prussian blue analogue. Taking potassium-based Prussian blue analogue (K2FeFe(CN)6·2.3H2O, KFF) as an example, P3HT@KFF is synthesized. The flow chart is as Figure 1 shown, and specifically includes the following steps:
[0044] A) Add poly(3-hexylthiophene) (P3HT) to chloroform and stir to fully dissolve to obtain a P3HT solution.
[0045] B) Add KFF powder to the P3HT solution and stir for 0.5 - 12 hours to obtain a suspension.
[0046] C) Centrifuge the obtained suspension to obtain a solid sample.
[0047] D) Put the solid sample into an oven and heat it for drying (dry at 80°C for more than 10 h) to obtain a dried P3HT@KFF sample.
[0048] The following will be further described in combination with specific examples and comparative examples.
[0049] Example 1
[0050] A coating modification method for a Prussian blue analogue is provided. Taking a potassium-based Prussian blue analogue (K2FeFe(CN)6·2.3H2O, KFF) as an example, P3HT@KFF is synthesized. The method specifically comprises the following steps:
[0051] Add poly 3-hexylthiophene (P3HT) to chloroform and stir at a mass ratio of 1:20 until fully dissolved. Add KFF powder and stir at a mass ratio of P3HT to KFF of 3:100. Stir for 0.5 to 12 hours at room temperature (20-30°C) to obtain a suspension. Centrifuge the obtained suspension to obtain a solid sample. Heat and dry the solid sample in an oven (dry at 80°C for more than 10 hours) to obtain dry P3HT@KFF. The sample obtained in this example is recorded as P3HT@KFF-3% or P3HT@KFF 80°C.
[0052] Example 2
[0053] A coating modification method for a Prussian blue analogue is different from Example 1 in that the mass ratio of P3HT to KFF in this example is 1:20, and other raw materials and methods are the same as those in Example 1. The sample prepared in this example is recorded as P3HT@KFF-5%.
[0054] Example 3
[0055] A coating modification method for a Prussian blue analogue is different from Example 1 in that the mass ratio of P3HT to KFF in this example is 1:10, and other raw materials and methods are the same as those in Example 1. The sample prepared in this example is recorded as P3HT@KFF-10%.
[0056] Comparative Example 1
[0057] The original potassium-based Prussian blue analog (K2FeFe(CN)6·2.3H2O, KFF) was used as a control sample without coating modification. The sample was placed in an oven for heating and drying (at 80°C for more than 10 hours) to obtain dry KFF. The sample obtained in this example is recorded as KFF or KFF 80°C.
[0058] Comparative Example 2
[0059] A coating modification method for a Prussian blue analogue is different from Example 1 in that the drying temperature of the solid sample is 150°C, and other raw materials, amounts and steps are the same as those in Example 1. The sample prepared in this example is recorded as P3HT@KFF 150°C.
[0060] Performance Testing
[0061] 1) Test the XRD patterns of the samples of Example 1 and Comparative Examples 1-2. Figure 2 The XRD patterns of the samples of Example 1 and Comparative Examples 1 to 2 are shown in FIG. Figure 2 It can be seen that too high a drying temperature will cause the material to decompose, and the sample of Comparative Example 2 is no longer in the Prussian blue phase. Since P3HT has a high solubility in chloroform, chloroform is used as a solvent in Example 1 and Comparative Example 2. Chloroform has a low boiling point, and the drying temperature does not need to be very high, 80°C is sufficient. If the temperature is too high, such as around 150°C, both the Prussian blue analog crystals and P3HT may decompose, seriously affecting the material properties. It can be seen that although increasing the drying temperature is beneficial to removing crystal water, it is necessary to keep the drying temperature within a certain range, which is more conducive to improving the comprehensive properties of the material.
[0062] 2) The electrochemical properties of the samples of Example 1 and Comparative Examples 1 to 3 were tested. The testing process was as follows: KFF of Comparative Example 1 and P3HT@KFF of Examples 1 to 3 were used as the positive electrode of the battery, metallic potassium was used as the negative electrode of the battery, 0.8 mol / L KPF6 (solvent was ECDEC) was used as the electrolyte, and glass fiber was used as the separator to assemble a potassium ion battery, and a constant current charge and discharge test was performed at 50 mA / g.
[0063] Figure 3 The electrochemical performance diagram of the samples of Examples 1 to 3 and Comparative Example 1 shows that the capacity retention rate of the sample KFF in Comparative Example 1 is only 41.12% after 200 charge and discharge cycles; while in Example 2, the P3HT@KFF-5% obtained after 5% P3HT coating can reach a capacity retention rate of 90.28% after 200 charge and discharge cycles, and the cycle stability is significantly improved. After 200 charge and discharge cycles, the capacity retention rates of Examples 1 and 3 are 81.33% and 76.05%, respectively, which are slightly worse than that of Example 2.
[0064] 3) The infrared spectra of the samples of Examples 1 to 3 and Comparative Example 1 (not subjected to cycle test) were tested, and the samples were subjected to cycle performance test using the performance test 1) method, and the infrared spectra of the samples after 10 cycles were measured.
[0065] Figure 4 The infrared spectra of the samples of Example 2 and Comparative Example 1 before and after the cycle test are shown in FIG. Figure 5The infrared spectra of the samples of Example 1 and Example 3 before and after the cycle test, wherein KFF, P3HT@KFF-3%, P3HT@KFF-5% and P3HT@KFF-10% represent the original samples before the cycle test, and KFF 10 cycles, P3HT@KFF-3% 10 cycles, P3HT@KFF-5% 10 cycles and P3HT@KFF-10% 10 cycles represent the samples after 10 cycles of the cycle test. It can be seen that for the original samples KFF and P3HT@KFF before the cycle test, their infrared spectra have a peak at 3400cm -1 and 1620cm -1 Strong absorption peaks appeared at 3400cm and 400cm, which correspond to the adsorbed water and coordinated water of Prussian blue analogs. -1 The adsorption peak of water at 1620 cm -1 The coordinated water peak at 3400cm becomes smaller, indicating that water will participate in the reaction and disappear during the charge and discharge process of KFF; while for P3HT@KFF, the original sample and the sample after 10 cycles have a smaller peak at 3400cm -1 The adsorption peak of water at 1620 cm -1 There is no obvious change in the coordinated water peak at , which shows that the coating modification of Examples 1 to 3 is not to reduce the water content in the crystal, but to confine it in the crystal so that it will not escape during the battery cycle and affect the battery performance. This coating modification method not only stabilizes the PBAs crystal structure, but also solves the problem of oxidative decomposition caused by the crystal water entering the battery electrolyte, and effectively improves the battery cycle performance.
[0066] 4) The water content of the samples of Examples 1 to 3 and Comparative Example 1 (not subjected to cycle test) was tested, and the samples were subjected to cycle performance test using the performance test 1) method to measure the water content of the samples after 10 cycles, as well as the initial charge and discharge specific capacity of the battery and the 200-cycle cycle capacity retention rate. The results are recorded in Table 1.
[0067] Table 1 Performance of samples of Examples 1 to 3 and Comparative Example 1
[0068]
[0069] As can be seen from Table 1, Examples 1 to 3 use P3HT to coat and modify the PBAs crystals, which does not reduce the water content in the crystals, but can effectively improve the specific capacity and cycle performance of the battery. This is mainly because, in the present invention, P3HT mainly plays the role of isolating the entry and exit of water molecules, thereby achieving improved battery performance, which is completely different from the path of improving battery performance by reducing the water content of the crystals in the prior art. Generally speaking, PBAs crystals contain crystal water. During battery operation, the crystal water enters the interior of the battery, which will cause the internal resistance of the battery to increase. In Example 1, P3HT confines the crystal water in the crystal lattice of PBAs. When the battery is running, the crystal water is confined in the crystal lattice and will not have a negative impact on the battery's performance, thereby achieving the purpose of improving battery performance. In addition, the crystal water in the crystal also has the function of promoting the improvement of battery performance. For example, it can shield K + Or Na + Interaction with structural anions, thereby increasing the K + Or Na + diffusion capacity, further improving the electrochemical performance of PBAs.
[0070] The method in the embodiment of the present invention can be applied to the finished PBAs containing a large amount of crystal water without changing its crystal structure. The method has a wide range of applications and is conducive to fundamentally solving the adverse effects of crystal water on PBAs. It has the advantages of good safety, low price, high capacity and high cycle life when applied to the positive electrode of the battery. When the modified Prussian blue analogue prepared in the embodiment of the present invention is used as the positive electrode material of potassium ion battery or sodium ion battery, the presence of crystal water in the crystal can also shield K + Or Na + Interaction with structural anions, thereby increasing the K + Or Na + The coating modification method in the embodiment of the present invention is simple, and the obtained modified Prussian blue analogue has good electrochemical performance and is widely used in the preparation of battery positive electrode materials, especially positive electrode materials of potassium ion batteries or sodium ion batteries.
[0071] In summary, the present invention uses poly 3-hexylthiophene (P3HT) to coat the Prussian blue analogue, and the crystal water is restricted in the crystal structure, so that it cannot escape during use, which effectively improves the structural stability of the modified Prussian blue analogue and improves its performance. When the modified Prussian blue analogue obtained by the method of the present invention is used as a positive electrode material for a battery, the crystal water can be prevented from escaping during the battery cycle. While stabilizing the crystal structure of the positive electrode material, the oxidative decomposition problem caused by the crystal water entering the battery electrolyte is solved, and the battery cycle performance is effectively improved. Therefore, the modified Prussian blue analogue of the present invention has a wide range of applications in the preparation of positive electrode materials for batteries.
Claims
1. A coating modification method for a Prussian blue analogue, characterized in that: The following steps are involved: Poly (3-hexylthiophene), a Prussian blue analogue and a solvent are mixed so that at least a portion of the poly (3-hexylthiophene) covers the Prussian blue analogue, and the coated and modified Prussian blue analogue is obtained after removing the solvent.
2. The coating modification method according to claim 1, characterized in that: The solvent includes at least one of chloroform, carbon disulfide, chlorobenzene, toluene, tetrahydrofuran, o-dichlorobenzene, p-dichlorobenzene or dimethylformamide.
3. The coating modification method according to claim 1, characterized in that: The chemical formula of the Prussian blue analogue is A y M′[M″(CN)6] y ·nH2O, where 0 < x ≤ 2, 0 < y ≤ 1, 0 < n ≤ 4, and A is an alkali metal element, and M′ and M″ are each independently transition metal elements.
4. The coating modification method according to claim 3, characterized in that: The alkali metal element includes at least one element selected from the group consisting of Li, Na, and K; And / or, the transition metal element includes at least one element selected from the group consisting of Fe, Co, Cu, Mn and Ni.
5. The coating modification method according to claim 1, characterized in that: The mass ratio of the poly 3-hexylthiophene to the Prussian blue analogue is 1:(10-35); And / or, the mass ratio of the poly 3-hexylthiophene to the solvent is 1:(15-25).
6. The coating modification method according to claim 1, characterized in that: The mixing time is 0.1 to 20 hours.
7. The coating modification method according to claim 1, characterized in that: The method of removing the solvent is drying; the drying temperature is 60 to 100° C.; and / or the drying time is 5 to 30 hours.
8. A modified Prussian blue analogue obtained by the coating modification method according to any one of claims 1 to 7.
9. The modified Prussian blue analogue according to claim 8, characterized in that The water content of the modified Prussian blue analogue is 10-15 wt %.
10. Use of the modified Prussian blue analogue according to claim 8 or 9 in preparing a positive electrode material for a battery.
Citation Information
Patent Citations
A method for modifying Prussian blue and its analogues and a sodium ion battery
CN109065883A
Preparation method of aqueous zinc ion battery positive electrode material
CN116154117A
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN116598490A
Dewatering and coating method and application of Prussian blue sodium ion battery positive electrode material
CN117154079A
Preparation method and application of conducting polymer in-situ coated manganese-based Prussian blue compound composite material
CN117276539A